Determination of Plant Available Nitrogen of Erzurum Plain Soils - YILDIZ, NESRIN; BILGIN, NURAY; BARIK, KENAN (Asian Journal of Chemistry, 2010)
The purpose of this investigation is to determine most suitable chemical extraction method(s) for determining plant available nitrogen in Erzurum plain soils. For this purpose 22 representative soil samples (cultivated and uncultivated) were sampled. A glasshouse experiment was conducted using randomized block design, each test plant replicated three times. Corn (Zea mays L.Var. Karadeniz Yildizi) plants were harvested 8 weeks after germination and dry matter, nitrogen and total nitrogen uptake of the test plants were determined. In order to determine available nitrogen contents of soils, 10 different chemical methods were used. On the other hand, in order to select the most suitable chemical extraction methods mainly, dry matter content, nitrogen content and nitrogen uptake of test plants were taken as biological indexes. The results of the correlation analysis showed clearly reported methods gave the highest correlation with biological indexes. As a results of data obtained it may be concluded that the most suitable chemical methods may be used in determining available nitrogen contents of Erzurum plain soils.